2024
DOI: 10.3390/agriculture14020312
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Performance of Sunflower Threshing Machines through Innovative Enhancements

Khaled Abdeen Mousa Ali,
Changyou Li,
Han Wang
et al.

Abstract: Improving the performance of the threshing process is of utmost importance in enhancing the quality of sunflower seeds and minimizing power consumption in sunflower production. In this study, we developed a modified sunflower threshing machine by incorporating two types of threshing rotors, namely the angled rasp bar rotor and the tine bar rotor, as compared to the round bar rotor. The performance of these rotors was evaluated under various rotational speeds (150, 200, 250, and 300 rpm) and concave clearances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Figure 5 illustrates the relationship between the machine's throughput in (kg/h) and the rotational speed of the drum for different configurations of brush peeling rows on the drum. The obtained data showed that the increase in drum rotational speed from 100 to 400 rpm corresponded with an increase in machine throughput, in line with [24,29]. Meanwhile, an increase in the number of brush peeling rows on the drum was found to be associated with a decrease in machine throughput.…”
Section: Machine's Throughputmentioning
confidence: 53%
“…Figure 5 illustrates the relationship between the machine's throughput in (kg/h) and the rotational speed of the drum for different configurations of brush peeling rows on the drum. The obtained data showed that the increase in drum rotational speed from 100 to 400 rpm corresponded with an increase in machine throughput, in line with [24,29]. Meanwhile, an increase in the number of brush peeling rows on the drum was found to be associated with a decrease in machine throughput.…”
Section: Machine's Throughputmentioning
confidence: 53%